Morphometric and microscopic evaluation of the effect of gallium nitrate as a root canal dressing in rat teeth submitted to late replantation - Mori, Graziela Garrido (2006)
The purpose of this study was to test a gallium nitrate solution, a resorption inhibitor, employed as a root canal dressing in teeth submitted to late replantation. Thirty maxillary right central incisors of rats were avulsed and kept dry for thirty minutes. The teeth were instrumented and the root surfaces were treated with 1% hypochlorite solution followed by application of 2% sodium fluoride. Thereafter, the teeth were divided into two groups according to the root canal dressing: Group I, solution of gallium nitrate; and Group II, calcium hydroxide paste. The teeth were then replanted in their respective sockets. The animals were killed at 15, 30 and 60 days after replantation and the samples were processed for morphometric and microscopic analysis. The results demonstrated that the gallium nitrate solution and the calcium hydroxide paste limited the root resorption, yet they did not impair its occurrence. It may be concluded that gallium nitrate solution and calcium hydroxide paste demonstrated similar performance.